Effective manual cleaning as the first step of reprocessing glass probes of a medical device for non-invasive physical plasma therapy - Röcker, Roland; Eggers, Benedikt; Kramer, Axel; Stope, Matthias B. (German Medical Science GMS Publishing House, 2024)
Background: For reusable devices and device components, effective reprocessing is essential to prevent nosocomial infections.Aim: The objective of the study was to evaluate manual cleaning as the first step of reprocessing reusable glass probes of a device for generation of non-invasive physical plasma, in accordance with regulations.Methods: Two glass probes of the device were contaminated with human blood. For manual cleaning, both probes were cleaned with instrument cleaning agent and instrument brushes. Cleaning efficacy was evaluated by total protein measurement in the rinsing solution.Results: After manual cleaning of the two test glass probes, no protein from the test contamination with human blood could be detected. Neither the different design of the two probes nor the use of a hard or a soft instrument brush demonstrated any difference.Conclusion: Our data suggest that manual cleaning of glass probes achieves complete removal of organic contaminants. This should enable safe applications in clinical practice.